The real driving emissions characteristics of light-duty diesel vehicle in four typical cities with varying altitudes in China - Haojie Gao; Rui Wang; Zhisong Wen; Xin Xiong; Zhuan Zheng; Shengqiang Lin; Hongchun Ding; Wenbin Tan (Case Studies in Thermal Engineering)
Real driving emissions (RDE) tests were conducted on a China VI B compliant light-duty diesel vehicle in four cities with different altitudes. The emission factors of particle number (PN), nitrogen oxides (NOx), and carbon monoxide (CO) were calculated using the carbon dioxide (CO2) moving average window (MAW) method and compared across different altitudes and driving stages. The tests covered urban, rural, and motorway sections in these four cities. The results showed that NOX and CO emissions were highest in urban sections. The study also analyzed the impact of altitude, traffic conditions, and exhaust temperature on emission characteristics. The results indicated that CO and NOX emissions increased with altitude, while PN emissions showed different trends due to aftertreatment effects. In high-altitude areas, CO and PN emissions also increased with higher cylinder and exhaust temperatures. The emissions of all pollutants were significantly lower than the China VI b emission standards. We suggest further research to optimize aftertreatment systems to better control emissions and improve efficiency under varying altitudes and route conditions.